2016
DOI: 10.3389/fphar.2016.00271
|View full text |Cite
|
Sign up to set email alerts
|

miR-200c Regulation of Metastases in Ovarian Cancer: Potential Role in Epithelial and Mesenchymal Transition

Abstract: Among the gynecological malignancies, ovarian cancer is the most fatal due to its high mortality rate. Most of the identified cases are epithelial ovarian cancer (EOC) with five distinct subtypes: high-grade serous carcinoma, low-grade serous carcinoma, mucinous carcinoma, endometrioid carcinoma, and clear-cell carcinoma. Lack of an early diagnostic approach, high incidence of tumor relapse and the heterogenous characteristics between each EOC subtypes contribute to the difficulties in developing precise inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 191 publications
2
56
0
Order By: Relevance
“…The EMT, the biological process by which epithelial cells are transformed into stromal EMT is characterized by a series of reversible molecular and phenotypic alterations and increased cell motility that promote the biological aggressiveness of malignant cells, such as invasion and metastasis [38,39]. Recent accumulating evidence has indicated that miRNAs [23].…”
Section: Mir-592 Promotes the Pi3k/akt And Mapk/erk Signaling Pathwaymentioning
confidence: 99%
“…The EMT, the biological process by which epithelial cells are transformed into stromal EMT is characterized by a series of reversible molecular and phenotypic alterations and increased cell motility that promote the biological aggressiveness of malignant cells, such as invasion and metastasis [38,39]. Recent accumulating evidence has indicated that miRNAs [23].…”
Section: Mir-592 Promotes the Pi3k/akt And Mapk/erk Signaling Pathwaymentioning
confidence: 99%
“…The functional involvement of miRNAs in OC initiation, development, and spread has been widely demonstrated. Furthermore, their potential use as biomarkers and for therapy has also been explored [90][91][92][93]. Most miRNAs play crucial cellular roles, participating in almost all molecular signaling pathways known to regulate cancer cell initiation, progression, metastasis, and survival.…”
Section: Targeting Lncrna and Mirna Network For Therapeutic Developmentmentioning
confidence: 99%
“…In order for these circulating tumor cells to adhere to endothelial cells in the new metastatic sites, they undergo mesenchymal-to-epithelial transition by recovering their epithelial properties. In contrast to the suppression of epithelial-to-mesenchymal transition by the miR-200 family, this metastatic colonization of tumor cells has been shown to be promoted by the miR-200 family [28]. Based on the results of this study, miR-200c is suggested to be highly expressed in tumor cells in the metastatic lymph nodes of our sample.…”
Section: Discussionmentioning
confidence: 62%